Geology and mineralization of the Hongqiling large magmatic nickel-copper-cobalt deposit (22×104 t) in Jilin Province, China: A review - Cong Chen; Yu-chao Gu; Di Zhang; Tao-tao Wu; Ai Li; Yun-sheng Ren; Qing-qing Shang; Jian Zhang; Xiong-fei Bian; Fei Su; Jia-lin Yang; Qiu-shi Sun; et al. (China Geology, 2024)
ABSTRACT: The Hongqiling large nickel-copper-cobalt deposit (hereafter referred to as the Hongqiling deposit), a typical mafic-ultramafic copper-nickel deposit in China, boasts proven Ni (Ni) resources of approximately 22×104 t, associated copper resources of 2×104 t, and associated cobalt (Co) resources of 0.5×104 t, with Ni reserves ranking 10th among China’s magmatic nickel deposits. Geotectonically, the Hongqiling deposit is situated in the superimposed zone between the Xing’an-Mongolian orogenic belt and the circum-Western Pacific’s active continental margin belt. Its ore-bearing plutons occur within the metamorphic rocks of the Ordovician Hulan Group, with the emplacement of plutons and the locations of orebodies governed by the deep-seated Huifahe fault and its secondary NW-trending Fujia-Hejiagou-Beixinglong-Changsheng fault zone. In the deposit, the rock assemblages of ore-bearing plutons predominantly encompass gabbro - pyroxenite - olivine pyroxenite - pyroxene peridotite (pluton No. 1) and noriteorthopyroxenite-harzburgite (pluton No. 7), with ore-bearing lithofacies consisting primarily of olivine pyroxenite and pyroxenite facies. The Hongqiling deposit hosts stratoid, overhanging lentoid, veined, and pure-sulfide veined orebodies. Its ores principally contain metallic minerals including pyrrhotite, pentlandite, chalcopyrite, violarite, and pyrite. Despite unidentified magma sources of ore-bearing mafic-ultramafic rocks, it is roughly accepted that the magmatic evolution in the Hongqiling deposit primarily involved fractional crystallization and crustal contamination. The ore-forming materials were primarily derived from the upper mantle, mixed with minor crustal materials. The ore-bearing mafic-ultramafic rocks in the deposit, primarily emplaced during the Indosinian (208–239 Ma), were formed in an intense extension setting followed by the collisional orogeny between the North China Plate and the Songnen-Zhangguangcai Range Block during the Middle-Late Triassic. From the perspective of the metallogenic geological setting, surrounding rocks, ore-controlling structures, and rock assemblages, this study identified one favorable condition and seven significant indicators for prospecting for Hongqiling-type nickel deposits and developed a prospecting model of the Hongqiling deposit. These serve as valuable references for exploring similar nickel deposits in the region, as well as the deep parts and margins of the Hongqiling deposit.